2015
DOI: 10.4269/ajtmh.14-0571
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Associated with Management of Buruli Ulcer/Human Immunodeficiency Virus Coinfection in a Treatment Center in Ghana: A Case Series Study

Abstract: Abstract. The synergy between Mycobacterium tuberculosis infection and human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome is well established but not so in Buruli ulcer (BU). We screened confirmed BU cases for HIV infection and followed seven BU/HIV-coinfected patients. Management of BU/HIV was based on the World Health Organization guidelines and patient condition. The HIV positivity among BU patients (8.2%; 11/134) was higher compared with that of general patients attending the facility (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 48 publications
(61 reference statements)
0
38
2
Order By: Relevance
“…Some studies have revealed association of mycobacteria infections with worsening peripheral blood cytopenia even though such has not been proven with MU infection . What is rather proven as a common cause of anemia in BU patients is nutritional anemia because the disease is mainly associated with persons of lower socioeconomic status . Susceptibility to BU is associated with polymorphism in the gene for the iron transporter protein NRAMP1 .…”
Section: Secondary Lesions Occurring After Bu Treatmentmentioning
confidence: 99%
“…Some studies have revealed association of mycobacteria infections with worsening peripheral blood cytopenia even though such has not been proven with MU infection . What is rather proven as a common cause of anemia in BU patients is nutritional anemia because the disease is mainly associated with persons of lower socioeconomic status . Susceptibility to BU is associated with polymorphism in the gene for the iron transporter protein NRAMP1 .…”
Section: Secondary Lesions Occurring After Bu Treatmentmentioning
confidence: 99%
“…And in TB/HIV co-infection, it is recommended that ART should be started 2 weeks into antimicrobial treatment. So, the optimal time to starting ART may depend on the specific co-infection and know interactions of some ART with the anti-microbial agents [5,35] . This combined effect of IRIS associated with HIV on ART and the paradoxical reactions experienced in BU patients on antimicrobial treatment could possibly lead to real challenge for BU/HIV coinfection management [5,12] .…”
Section: Komenan K Et Al Hiv/bu Co-infection Management In Africamentioning
confidence: 99%
“…So, the optimal time to starting ART may depend on the specific co-infection and know interactions of some ART with the anti-microbial agents [5,35] . This combined effect of IRIS associated with HIV on ART and the paradoxical reactions experienced in BU patients on antimicrobial treatment could possibly lead to real challenge for BU/HIV coinfection management [5,12] . HIV infection may affect the outcome of BU treatment such as mortality, time to healing, recurrence rate and the incidence of paradoxical reactions or IRIS [30] .…”
Section: Komenan K Et Al Hiv/bu Co-infection Management In Africamentioning
confidence: 99%
See 2 more Smart Citations